A Systematic Literature Review of Factors Influencing Satisfaction and Continuance Intention to Use E-Learning Systems in Higher Education - Alshammari, Maha Farhan; Yusoff, Rasimah Che Mohd; Abas, Hafiza (Advances in Social Sciences Research Journal, 2024)
Electronic learning (e-learning) allows students to access course materials without time or location constraints. While much research has focused on e-learning adoption or acceptance, there is a lack of studies examining students' satisfaction with Continuance Intention (CI) to continue using e-learning systems. This paper conducts a systematic review of existing research on this topic within higher education. An analysis of 34 articles identifies 42 factors influencing students’ satisfaction with CI. The review outlines the models and constructs used in the studies, revealing that many employed the Expectation Confirmation Model (ECM) to assess satisfaction. Key constructs consistently found to significantly impact students' satisfaction with CI include System Quality, Information Quality, Self-efficacy, Service Quality, Perceived Ease of Use, and Perceived Enjoyment.